EVALUASI PENCAPAIAN LABA PADA HOTEL SAHID KAWANUA MANADO DENGAN MENGGUNAKAN ANALISIS COST VOLUME PROFIT (CVP) - Bunga, Aristion; Ilat, Ventje; Afandy, Dhullo (Universitas Sam Ratulangi, 2018)
The problem in this research is how to evaluate the achievement of profit by using cost volume profit analysis (CVP) at Hotel Sahid Kawanua Manado, with the starting point from the backgound of competition and growth of hotels that increasingly mushrooming in Manado city. This study aims to determine the calculation and profit planning at Hotel Sahid Kawanua Manado by using sales operational data by using cost volume profit analysis (CVP) for multi product in 2015-2017, and to determine Break Even Point (BEP), profit planning and find out what level of margin of safety (minimum selling rate of company not to suffer losses) in year 2015-2017. The data used comes from literature study, observation and interview on the object of research. This data processing uses the help of Microsoft Excel 2016 program to perform the separation of semivariable costs into fixed costs and variable costs. Besed on the calculation of cost volume profit analysis (CVP), showed that Hotel Sahid Kawanua Manado has done the evaluation of the achievement of earnings well seen from the level of profit generated and the level of margin of safety is increasinng from year to year.Keywords : Cost Accounting, Cost Volume Profit Analysis (CVP), Earnings Achievement